The Embryology of Angiosperms - Bhatnagar, S.P. jt. (New Delhi : : Vikas Publishing House, 1974)
During the last two decades the modern techniques of histochemistry, electron microscopy, plant physiology, biochemistry, cell and molecular biology, immunology, and genetics have been applied to investigate the intricacies of the processes involved in embryo formation, and considerable new
Includes bibliographical references and index.
Keywords: Plant physiology; Angiosperms